Program Home Visit: Penguatan Perkembangan Nilai Agama dan Moral Anak Usia Dini di Era New Normal - Mumtazah, Durrotun; Sutama, Sutama (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2021)
The spread of the coronavirus (Covid-19) causes all activities and learning activities to be carried out from home. The home visit program is one of the programs at TK Ar-Rahman Tasikmadu Karanganyar in the new normal era. The purpose of this study was to describe the home visit program in strengthening the development of religious and moral values ​​in early childhood in Kindergarten Ar-Rahman Tasikmadu Karanganyar. This study used a descriptive qualitative approach with data collection using interviews, observation, and documentation. The research subjects were group A TK Ar-Rahman. Data analysis using a model developed by Miles and Huberman. The results showed that in the new normal era, the development of religious and moral values ​​in the TK A group in TK Ar-Rahman went well through the home visit program. The home visit program procedure consists of: planning, implementing, evaluating, and analyzing the results of the evaluation, follow-up, and reports. The aspect of religion being developed is that children can know their religion, children can imitate worship movements in the right order, children can say prayers before and/or after doing something, children can say greetings and return greetings. While the moral aspects include: children can recognize good, polite, and bad behavior, and children can get used to behaving well.